Clinical management of cutaneous bovine papillomatosis in a cow calf: a case report - Khan, S; Akbar, H; Rashid, MI; Younas, M; Farooqi, SH; Rehman, FUr; Badshah, A; Azeem, S (Journal of the Hellenic Veterinary Medical Society, 2022)
A Sahiwal breed heifer calf of ~ 5-month age was presented with numerous warts of varying sizes principally on head, face and neck. The history and clinical examination were suggestive of bovine cutaneous papillomatosis. The animal was treated medically with an alternative medicine: Thuja occidentalis 30X. The warts regressed completely after two months of treatment with Thuja occidentalis, suggesting this medicine can be used to treat warts in bovines successfully.